THE INITIATION CAUSES RESEARCH OF METAL VOIDS ON THE RAILWAY WHEELS THREAD - Gryshchenko, M. A. (Science and Transport Progress, 2008)
In the article the research results related to an origin of defects – crumbling out of metal on the tread contact surfaceof railway wheels – are presented.